Eastward spreading of the invasive Rugulopteryx okamurae (Heterokontophyta, Dictyotales) in the Mediterranean: first record in the Adriatic Sea - BOTTALICO, ANTONELLA; TURSI, ANDREA; MASTROTOTARO, FRANCESCO; CHIMIENTI, GIOVANNI; MINCUZZI, ANNAMARIA (Mediterranean Marine Science, 2024)
The brown seaweed Rugulopteryx okamurae is currently included in the list of invasive alien species of European Union concern due to its rapid expansion that is causing both ecological and economic impacts. In this study, we report the first record of R. okamurae in the Southern Adriatic Sea, off the coast of Bari, Italy, currently representing the easternmost limit of its distribution in the Mediterranean Sea. Morphological observations combined with rbcL and psbA sequence analyses confirmed the taxonomic identification. Field surveys carried out between April 2023 and January 2024 highlighted the conspicuous occurrence of R. okamurae over a total surface of approximately 6.5 ha. Two main human-mediated pathways occurring near the sites of the first observation of the alien species may have been responsible for its introduction: the trade in living organisms for human consumption and maritime transport related to the proximity of the port of Bari to the invaded area. Future studies will aim to identify and implement practical, cost-effective management strategies to mitigate this alarming bioinvasion.